The use of educational technologies in the Physical Culture career - Kaliane Valera-Rodríguez; Alfredo Maximiliano Soler-Agüero; Alejandro Rodríguez-Romero (Universidad de Guantánamo, 2018)
The use of information and communication technologies in pedagogical processes is an essential pillar in the current transformations of the different educational levels. This demands, the preparation of the future professor of Physical Culture in the use of different educational technologies from the subjects of the curriculum. However, there are no precisions for professors about this topic, limiting the development of skills of the graduates. The objective of this research is the proposal of methodological recommendations to facilitate the development of the teaching-learning process as a general contribution to the preparation of Physical Culture professors.